Direct chemical vapor deposition of CoO on Ni-foam for supercapacitor electrode applications - Joseph Anthony Duncan, Jr.; Farhan Azim; Alisha Dhakal; Himal Pokhrel; Sanjay R. Mishra; Shawn David Pollard (Next Materials)
Low-pressure chemical vapor deposition was used to grow cobalt oxide (CoO) directly on nickel foam using a Cobalt Chloride (CoCl2·6H2O) precursor. The resultant coating was evaluated with scanning electron microscopy, X-ray diffraction, and X-ray photoelectron spectroscopy, which revealed a disordered surface with significant growth of CoO throughout the three-dimensional porous structure. The electrochemical performance of the resultant structure was subsequently evaluated using electrochemical impedance spectroscopy (EIS), galvanostatic charge-discharge (GCD), and cyclic voltammetry, showing a maximum specific capacitance of 1.10 F/cm2 in a 1.0 M KOH aqueous solution at a 10 mV/s scan rate, significantly higher than that obtained for a control nickel foam electrode sample. Low charge transfer and solution resistances observed from EIS analysis suggested the influence of fast redox reactions at the CoO-coated Ni foam electrode-KOH electrolyte interface. The extended discharge times obtained from GCD measurements at low current densities demonstrate improved capacitive efficiency of the Ni-CoO electrode, thus making it a potential candidate in the field of energy storage application.